Political and judicial rights through the prism of religious belief - Sterkens, Carl; Ziebertz, Hans-Georg (Religion and human rights, 2018)
This innovative volume is focused on the relationship between religion on the one hand and political and judicial rights on the other. At a time when the so-called `checks and balances' that guarantee the vulnerable equilibrium between legislative, executive and judicial branches of governance are increasingly under pressure, this book offers valuable insights. It presents empirical work that has measured young people's attitudes and explains the variety found across their views. Readers will find answers to the question: To what extent do youths in different countries support political and judicial human rights and what influences their attitudes towards these rights? The political rights in this question include, among others, active and passive voting right, the right to protest, and the rights of refugees. Judicial rights refer in general to the right of a fair trial, and include principles like equality before the law; the right to independent and impartial judgement; the presumption of innocence; the right to legal counsel; and the privilege against self-incrimination. Expert contributing authors look at aspects such as religious beliefs and practices, personal evaluation of state authorities, and personality characteristics. The authors discuss contextual determinants for attitudes towards political and judicial rights, in both theory and empirical indicators. Numerous helpful tables and figures support the written word. This book makes an original contribution to research through the empirical clarification of factors that induce or reduce people's support of political and judicial rights. It will appeal to graduates and researchers in religious studies, philosophy or sociology of religion, among other disciplines, but it will also interest the general reader who is concerned with matters of human rights and social justice